2014
DOI: 10.1016/j.jval.2014.08.832
|View full text |Cite
|
Sign up to set email alerts
|

Quality Of Life Of Diarrheal Children And Caregivers In Thailand

Abstract: objeCtives: Liver transplantation is an effective treatment option for end-stage liver disease and acute liver failure, including patients with hepatitis C (HCV) and hepatitis B (HBV). Recent health technology assessments of treatments for HCV and HBV have relied on data from a large cohort study of transplanted patients to inform estimates of costs of liver tranplantations; however this was conducted in the 1990s. The overall aim of this study was to estimate the current cost of liver transplant for patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Both used the EQ5D for both parent and child (despite there being no validated value sets for children). The first study from Thailand [25] examined hospitalised children and rated the mean child's utility as 0.604 (95%CI: 0.592, 0.615) and parents of 0.618 (95%CI: 0.606, 0.629). The second study from Denmark [26] of all gastroenteritis attendances found median HRQoL of 0.7123 for children, and 0.818 for parents with a median length of illness of 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…Both used the EQ5D for both parent and child (despite there being no validated value sets for children). The first study from Thailand [25] examined hospitalised children and rated the mean child's utility as 0.604 (95%CI: 0.592, 0.615) and parents of 0.618 (95%CI: 0.606, 0.629). The second study from Denmark [26] of all gastroenteritis attendances found median HRQoL of 0.7123 for children, and 0.818 for parents with a median length of illness of 7 days.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, few studies have used multiple assessments to measure the effect of an acute illness on QOL for the entire episode, as most studies assess HRQOL only at presentation to a health-care facility. The limited number of studies assessing the association between rotavirus illness and QOL from Europe, North America and Thailand have estimated HRQOL to range from 0.604 to 0.896 in children and 0.618 to 0.875 in parents, where 1 indicates no effect of illness 169,170 . The differences between locations might be due to variations in the tools used, the type of health-care facility available and cultural determinants regarding when children are taken to a health-care facility.…”
Section: Quality Of Lifementioning
confidence: 99%